Mother's care-seeking behavior for neonatal danger signs from qualified providers in rural Bangladesh: A generalized structural equation modeling and mediation analysis - Azad, Rashidul; Billah, Sk Masum; Bhui, Bal Ram; Ali, Nazia Binte; Herrera, Samantha; Graft-Johnson, Joseph de; Garg, Lyndsey; Priyanka, Sabrina Sharmin; Zubair, Shams; Rokonuzzaman, S. M.; Rahman, Mohammad Mahmoodur; Meena, Umme Salma Jahan; et al. (Frontiers in Pediatrics, 2023)
Background Neonatal deaths contribute to nearly half (47%) of under-five mortality globally and 67% in Bangladesh. Despite high neonatal mortality, care-seeking from qualified providers for newborn danger signs remains low. Identification of direct and indirect factors and their pathways affecting care-seeking would help to design a well-targeted intervention. This study assessed the inter-relationship among predictive factors and neonatal care-seeking in Bangladesh. Materials and methods Data from 17,251 recently delivered women (RDW) with a live birth outcome in the past 15 months from a cross-sectional baseline household survey conducted in 14 districts of Bangladesh in 2019 were analyzed. We investigated the inter-relationship of maternal background characteristics, maternal health utilization factors, child/neonate factors, health service delivery related factors and newborn danger sign knowledge with newborn care-seeking practices and estimated the direct, indirect, and total effects using Generalized Structural Equation Modeling (GSEM) and mediation analysis. Results Out of 17,251 mothers, 8,765 mothers Half (50.8%) of mothers reported a neonatal illness and among them, only 36.5% of 8,765 mothers of sick neonates sought care from qualified providers. Our mediation analysis showed that maternal health utilization factors, i.e., 4+ antenatal care visits (ANC) from a qualified provider, facility delivery and postnatal care (PNC) from a qualified provider showed the highest total effect over other factors domains, and therefore, were the most important modifiable predictors for qualified neonatal care-seeking. Other important factors that directly and/or indirectly increased the chance of newborn care-seeking from qualified providers were household wealth, maternal education, distance to nearest health facility, community health workers (CHWs) home visits during ANC, neonatal danger sign counseling after delivery and women’s knowledge of neonatal danger signs. Conclusion The inter-relationship and highest summative effect of ANC, facility delivery and PNC on newborn care-seeking suggested the maternal care continuum altogether from ANC to facility delivery and PNC to improve sick newborn’s care-seeking. Additionally, referral training for unqualified providers, targeted intervention for poorer households, increasing CHWs home visits and neonatal danger sign counseling at the facility and community should also be considered.